PROGRAM KALESANG DESA SEBAGAI UPAYA PENGENTASAN KEMISKINAN PADA MASYARAKAT DESA - Mansyur Nawawi; Rudy Kurniawan; M. Chairul Basrun Umanailo; Hamiru Hamiru; Salma Yusuf (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
The village Kalesang Program is a government business of Buru Regency to improve the lives of the village community with participatory planning patterns that come from the government and society. The Kalesang village includes the planning and implementation of Village development conducted jointly between the Government and the village community. This research is a qualitative study aimed at describing the implementation of the village's Kalesang program as a poverty alleviation instrument in rural communities. The research location focuses on Lala, Namlea and Marloso with the consideration of different social-economic characters with other villages in Namlea subdistrict. The number of informants interviewed was 45 people divided into communities, village apparatus and community leaders. Analytical techniques used to follow the concept of Miles and Huberman where activities in the analysis of qualitative data are conducted interactively and continuously. The results showed that the village's Kalesang program was able to become a development instrument and empowerment that was able to foster cooperation from the Community and government to plan and implement development and to keep watching it Through active participation. The end goal of the village Kalesang in the form of poverty testing made easy in the frame of harmonization and synergy between the government and the community to cooperate in resolving the problem of Village development.